The Gestapo: power and terror in the Third Reich - Dams, Carsten (Oxford University Press, 2014)
Foundation and Early Years -- Development of the Organization -- Gestapo Collaborators -- How the Gestapo Worked -- Persecution in the Reich -- The Gestapo in Europe -- The Gestapo after 1945 -- Conclusion: what is left of the Gestapo?